Development of Google Slides Assisted Interactive Multimedia in Biology for Grade X High School - Anggreini; Zelhendri Zen; Darmansyah; Fetri Yeni J (Postgraduate, University of Mataram, 2025)
This study is motivated by the low student engagement and understanding of biology concepts due to the limited use of engaging learning media. At SMA N 4 Batam, although tools and technology are available, the use of effective media in teaching is still limited. The purpose of this study is to develop valid, practical, and effective biology learning media for grade X high school students. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validity of the media was tested by four experts: an instrument expert, a media expert, a language expert, and a content expert, while practicality testing was conducted by five educators and 34 students. The results show that the interactive multimedia developed is highly valid, practical, and effective. The validation results show that all tested instruments received a 100% score, categorized as